PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING MENGINTERPRETASI TEKS LAPORAN HASIL OBSERVASI PESERTA DIDIK KELAS X - Mulyati, Dewi Mulyati; Hariyadi, Hariyadi (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
The background is that students find it difficult to interpret the report text. The problem of how learning interprets the text of the observation report on class X students. The purpose of this study is describe the learning planning of interpreting the text of the observation report on class X students. This research method is classroom action research. The results of the study are as follows. (1) Based on the initial information questionnaire, it is known that 99.00% of class X students find it difficult to interpret the text of the observation report. (2) the average pre-cycle score shows that learning to interpret the text content of the observation report of class X is still lacking, namely 51.41. (3) The increase in the first cycle was 5.22. (4) Cycle II experienced an increase in score of 4.00. This increase is influenced by discovery learning and the problem of basic learning.